Exploring Rhetorical Approaches in Indonesian Master Thesis Introductions - Wakerkwa, Dian Agustina Purwanto (FKIP - Universitas Tanjungpura, 2025)
A thesis is a compulsory assignment that should be created at the end of the study by the master